EFFECT OF WORKING CAPITAL MANAGEMENT, SALES GROWTH AND LIQUIDITY ON PROFITABILITY IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE PERIOD 2018-2020 (JEM17: Jurnal Ekonomi Manajemen, 2022)
Capital markets play as vital role in supporting a country's economy considering that the capital market has two inviolable capacities, namely monetary capacity and monetary capacity. The capital market is a gathering place for parties who have abundant financial backer with people who need reserves (organizations) by exchanging protection. The presence of capital markets plays an important role for financial backers, both individual financial backers and business elements. They can channel very large abundant assets to donate, so that business people can get additional assets to expand their business network from financial backers in the capital market. Associative research, a sort of research used to determine the association between two variables, was employed in this study. These methodologies and types of investigations are used to look at the impact of working capital management, sales growth, and liquidity on profitability in manufacturing companies. The coefficient of determination (R-Squared) is 0.693909, which equals 69 percent. This shows that the contribution of independent factors consisting of two, namely financial management and liquidity to profitability by 69%, remaining (100% - 69% = 31%) various variables have an impact and beyond variables. Working capital management has a significant impact on profitability, as measured by cash and inventory turnover. Although receivables turnover may not have a significant influence on profitability, it motivates the firm to enhance its receivable management so that receivables can be converted into cash and used for the company's operational purposes as promptly as possible. Keywords : Working capital management, sales growth, liquidity, and profitability.